Hydrophilic wear-resistant photovoltaic coating with photocatalytic effect and preparation method thereof

By using hydrophilic nanomaterials and polymer cross-linking technology, hydrophilic wear-resistant photovoltaic coatings with photocatalytic effects are prepared, which solves the problem that existing photovoltaic coatings are susceptible to pollution and moisture in outdoor environments, achieves efficient self-cleaning and good wear resistance, and improves the service life and power generation efficiency of photovoltaic panels.

CN119875444APending Publication Date: 2025-04-25BEIJING RISHENG CHANGLONG ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510130012.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing photovoltaic coatings are susceptible to dust, dirt and moisture in outdoor environments, resulting in reduced power generation efficiency, poor self-cleaning capacity and insufficient wear resistance.

Method used

The hydrophilic nanosilicon dioxide, hydrophilic nanozirconia, hydrophilic nanotitanium dioxide, polyvinyl alcohol and glutaraldehyde were used to prepare hydrophilic wear-resistant photovoltaic coatings with photocatalytic effects through spraying method to build a microscopic hydrophilic network and a solid crosslinking structure.

Benefits of technology

It realizes efficient self-cleaning of the coating, excellent hydrophilicity and good wear resistance, extends the service life of the photovoltaic panel, and improves power generation efficiency and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875444A_ABST
    Figure CN119875444A_ABST
Patent Text Reader

Abstract

The invention provides a hydrophilic wear-resistant photovoltaic coating with a photocatalytic effect and a preparation method thereof, and relates to the technical field of wear-resistant coatings, the raw materials of the coating comprise hydrophilic nano silica, hydrophilic nano zirconia, hydrophilic nano titanium dioxide, polyvinyl alcohol, glutaraldehyde and ethanol. The invention also provides a preparation method of the coating, which comprises the following steps: putting the hydrophilic nano silicon dioxide, the hydrophilic nano zirconium oxide and the hydrophilic nano titanium dioxide into ethanol to obtain an inorganic powder suspension; mixing polyvinyl alcohol with distilled water to obtain a polyvinyl alcohol aqueous solution; adding a polyvinyl alcohol aqueous solution into the inorganic powder suspension to obtain a mixed solution, and adding glutaraldehyde to obtain a spraying solution; and spraying the spraying solution onto a photovoltaic panel, and performing cross-linking and curing to obtain the hydrophilic wear-resistant photovoltaic coating with the photocatalytic effect. The coating disclosed by the invention is good in wear resistance, excellent in adhesiveness and very good in self-cleaning capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wear-resistant coatings, and in particular to a hydrophilic wear-resistant photovoltaic coating with a photocatalytic effect and a preparation method thereof. Background Art

[0002] In today's energy and materials science fields, with the growing demand for renewable energy, photovoltaic technology has developed rapidly as an important representative of clean energy. As the core component of the photovoltaic system, the performance and service life of solar panels have attracted much attention.

[0003] Most traditional photovoltaic coatings focus only on improving the efficiency of photoelectric conversion, while ignoring many problems in the actual use environment. On the one hand, in outdoor environments, impurities such as dust and dirt can easily adhere to the surface of photovoltaic panels. Since photovoltaic panels are usually installed at high places or in relatively open areas, manual cleaning is difficult and costly, and frequent cleaning may cause wear on the panel surface, affecting its optical properties and mechanical strength, thereby reducing power generation efficiency. According to relevant studies, the power generation efficiency of photovoltaic panels can drop by 10%-30% within a few months simply due to dust accumulation.

[0004] On the other hand, if the coating does not have good hydrophilicity, moisture in the outdoor environment such as rain and dew will easily form residual water droplets, which may produce a lens effect under the sun, focusing and burning the panel surface, and also provide a breeding ground for microorganisms, accelerating panel aging. In addition, some existing hydrophilic coatings often have poor wear resistance. Under mechanical effects such as wind and sand erosion, daily maintenance and wiping, the coating is easy to fall off and fail, and cannot function stably for a long time.

[0005] Photocatalytic technology has gradually emerged in recent years. Its principle is to use the strong oxidizing substances produced by photocatalysts under light conditions to decompose organic pollutants. In theory, it can provide a new idea for solving the problem of photovoltaic panel surface cleaning. However, the technology of organically combining the photocatalytic effect with hydrophilicity and wear resistance and adapting it to photovoltaic coatings is still in the exploratory stage. Existing products or technical solutions are difficult to simultaneously meet the comprehensive requirements of efficient photocatalysis, excellent hydrophilicity and good wear resistance, which greatly reduces the stability and continuous power generation capacity of photovoltaic panels in long-term outdoor operation.

[0006] The photovoltaic coatings in the prior art have poor hydrophilicity, weak wear resistance and poor self-cleaning ability. Summary of the invention

[0007] The invention provides a hydrophilic wear-resistant photovoltaic coating with photocatalytic effect and a preparation method thereof, so as to solve the technical problems of poor wear resistance, easy peeling and poor self-cleaning ability of the photovoltaic coating in the prior art.

[0008] To achieve the above-mentioned purpose, the present invention provides a hydrophilic wear-resistant photovoltaic coating with photocatalytic effect, the raw materials of which include hydrophilic nano-silicon dioxide, hydrophilic nano-zirconium oxide, hydrophilic nano-titanium dioxide, polyvinyl alcohol, glutaraldehyde and ethanol.

[0009] Preferably, the raw materials include, by mass, 0.3-0.8 parts of hydrophilic nano-silicon dioxide, 0.5-1 parts of hydrophilic nano-zirconium oxide, 2-2.5 parts of hydrophilic nano-titanium dioxide, 0.3-0.5 parts of polyvinyl alcohol, 0.08-0.1 parts of glutaraldehyde and 90 parts of ethanol.

[0010] Preferably, the average particle size of the hydrophilic nano-silica is 10-20 nm.

[0011] Preferably, the average particle size of the hydrophilic nano-titanium dioxide is 20-30 nm.

[0012] A method for preparing a hydrophilic, wear-resistant photovoltaic coating having a photocatalytic effect as described above comprises the following steps: S1, putting hydrophilic nano-silicon dioxide, hydrophilic nano-zirconium oxide and hydrophilic nano-titanium dioxide into ethanol to obtain an inorganic powder suspension; S2, mixing polyvinyl alcohol with distilled water, dissolving the polyvinyl alcohol under a water bath condition, and obtaining a polyvinyl alcohol aqueous solution; S3, adding the polyvinyl alcohol aqueous solution to the inorganic powder suspension to obtain a mixed solution, adjusting the pH value of the mixed solution, adding glutaraldehyde, and stirring to obtain a spray solution; S4, spraying the spray solution onto the photovoltaic panel, and obtaining a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect after cross-linking and curing.

[0013] Preferably, the mass concentration of the polyvinyl alcohol aqueous solution in S2 is 12-18%.

[0014] Preferably, the water bath temperature in S2 is 98-100°C.

[0015] Preferably, the pH value in S3 is 4-6.

[0016] Preferably, during the spraying process in S4, the pressure of the spray gun is 0.2-0.4 MPa, and the spray distance (the distance between the spray gun and the sprayed surface) is 15-25 cm.

[0017] Preferably, the thickness of the hydrophilic and wear-resistant photovoltaic coating with photocatalytic effect is 80-120 nm.

[0018] In the present invention, hydrophilic nano-silicon dioxide, hydrophilic nano-zirconia and hydrophilic nano-titanium dioxide are dispersed in a network system after cross-linking of polyvinyl alcohol and glutaraldehyde. These nano-scale hydrophilic materials have unique surface structures and chemical properties, and they can construct a microscopic hydrophilic network on the surface of the coating. Taking hydrophilic nano-silicon dioxide as an example, its surface is rich in a large number of hydroxyl (-OH) groups, which can form hydrogen bonds with water molecules, making it very easy for water molecules to spread on the surface of the coating instead of forming water droplets. When water contacts the coating, the water molecules will be quickly adsorbed by these hydrophilic groups and evenly distributed on the surface, thereby giving the coating excellent hydrophilicity, ensuring that water quickly slides off, taking away impurities such as surface dust, and effectively preventing adverse effects such as lens effects caused by residual water droplets.

[0019] Polyvinyl alcohol, as a high molecular polymer with good water solubility and film-forming properties, undergoes a cross-linking reaction with glutaraldehyde. It can form chemical bonds between molecules, tightly connect the various components together, and build a solid three-dimensional network structure. This cross-linking structure greatly improves the cohesion and deformation resistance of the coating, making it less likely to crack or peel off when subjected to external impact or friction, further enhancing the wear resistance of the coating.

[0020] It helps build a hydrophilic structure in the coating system. On the one hand, the hydroxyl groups on its molecular chain can work synergistically with the nano hydrophilic material to enhance the adsorption capacity of water molecules; on the other hand, it can fill between nano particles during the film-forming process, making the coating structure more dense and uniform, further ensuring the consistency of hydrophilicity on the entire coating surface.

[0021] Hydrophilic nano-zirconia has high hardness and good chemical stability, and plays the role of a "skeleton" in the coating to enhance wear resistance. It is evenly dispersed in the coating system. When subjected to external mechanical friction, such as wind and sand blowing, wiping and other forces, the nano-zirconia particles can withstand greater friction and prevent the coating surface from being easily scratched or abraded. At the same time, it cooperates with hydrophilic nano-silicon dioxide and hydrophilic nano-titanium dioxide to form a tight composite structure. The mutual interlocking between these nanoparticles makes the overall coating have higher mechanical strength, effectively resisting wear and tear in daily use, ensuring that the coating is stably attached to the surface of the photovoltaic panel for a long time and maintaining its performance.

[0022] In addition, under light conditions, especially when exposed to ultraviolet rays, the valence band electrons of hydrophilic nano-titanium dioxide will be excited to jump to the conduction band, generating electron-hole pairs. Holes are extremely oxidizing and can react with water molecules or hydroxyls adsorbed on the surface to generate hydroxyl radicals (・OH) with strong oxidizing properties. At the same time, electrons combine with oxygen molecules in the air to generate superoxide anion radicals (・O2⁻). These free radical active species can attack organic components in bird droppings, such as complex macromolecules such as proteins, fats, and carbohydrates, and gradually decompose them into small molecules of carbon dioxide, water, and harmless substances such as inorganic nitrides, thereby achieving the self-cleaning function of bird droppings. Even if bird droppings are attached to the surface of the photovoltaic coating for a long time, as long as there is light, the photocatalytic reaction will continue, slowly but effectively decomposing the bird droppings, avoiding its continued negative impact on the lighting and power generation performance of the photovoltaic panel, keeping the panel surface clean, and ensuring power generation efficiency. The smaller particle size of hydrophilic nano-titanium dioxide shortens the diffusion path of photogenerated carriers, allowing more photogenerated carriers to participate in the photocatalytic reaction, generating more active substances such as hydroxyl radicals and superoxide anion radicals, thereby enhancing the self-cleaning function of the coating.

[0023] The present invention makes full use of the structural-functional synergistic effect of organic-inorganic composite materials to solve the application requirements of hydrophilic, wear-resistant and self-cleaning photovoltaic coatings. Polyvinyl alcohol and glutaraldehyde are cross-linked with the surface hydroxyl groups of inorganic particles to give the coating a certain toughness and structural strength, low-refractive nano-silicon dioxide provides the main anti-reflection structure, hydrophilic zirconium oxide improves the wear resistance of the coating, and hydrophilic nano-titanium dioxide provides a self-cleaning function.

[0024] In the present invention, hydrophilic nano-silicon dioxide is used as the adsorption and dispersion medium of the bottom layer, and its abundant hydroxyl groups interact with other nano-particles. Hydrophilic nano-titanium dioxide is evenly dispersed in this system and exerts a photocatalytic effect under light. Hydrophilic nano-zirconia is embedded in it, which plays the dual functions of enhancing hardness and improving the transmission of photogenerated carriers.

[0025] Compared with the prior art, the present invention has the following beneficial effects: Hydrophilic nano-titanium dioxide is the core component of photocatalysis. It produces electron-hole pairs under light, which can effectively oxidize and decompose organic matter adsorbed on the surface of the coating, making the coating self-cleaning. It can decompose pollutants such as dust and oil, reduce the accumulation of dirt on the surface of photovoltaic modules, maintain high light transmittance, and ensure stable photovoltaic performance.

[0026] Hydrophilic nano-zirconia interacts with titanium dioxide, promoting the separation and transmission of photogenerated carriers, reducing the probability of electron-hole pair recombination, and improving photocatalytic efficiency; polyvinyl alcohol can fix titanium dioxide, ensure the stability and effective distribution of active sites, optimize the adsorption and desorption of reactants, and indirectly enhance the photocatalytic effect; hydrophilic nano-silica is conducive to the dispersion of nanoparticles and increases the photocatalytic reaction area.

[0027] Hydrophilic nano-silica, hydrophilic nano-zirconia and polyvinyl alcohol and other ingredients give the coating good hydrophilicity, allowing water to form a uniform water film on the surface of the coating, accelerating the loss of pollutants with water, avoiding the adhesion of pollutants, and making the coating have good self-cleaning ability. In addition, the hydrophilicity of the coating can reduce the adhesion of pollutants such as dust and oil on the surface of the coating, reduce the possibility of photovoltaic modules being contaminated, extend the cleaning cycle of the modules, and reduce the cost and frequency of manual cleaning.

[0028] Hydrophilic nano-zirconia fills the microscopic voids in the coating, reduces defects and enhances the hardness of the coating with its high hardness and chemical stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the hydrophilic wear-resistant photovoltaic coating with photocatalytic effect provided in Example 1; Figure 2 This is a physical picture of the photovoltaic panel with bird droppings in Example 1; Figure 3 This is a photo of the photovoltaic panel with bird droppings in Example 1 after being decomposed for 7 days. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme of the embodiment of the present invention will be clearly and completely described in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative labor belong to the scope of protection of the present invention. Hydrophilic nano-silicon dioxide: Shandong Gongpai / Jining Sunless Biotechnology Co., Ltd., item number 60676-86-0, the hydrophilic nano-silicon dioxide provided has a purity of >99%; hydrophilic nano-titanium dioxide: Xuancheng Jingrui New Materials Co., Ltd., VK-T06H nano-titanium dioxide is hydrophilic, white powder, rutile crystal form; hydrophilic nano-zirconium oxide: Zhejiang Jinkun Zirconium Industry Co., Ltd., item number jk-3y-zn; polyvinyl alcohol: Wuhan Huaxiang Kejie Biotechnology Co., Ltd., item number 9002-89-5 PVA17-88, degree of polymerization is 1700, and degree of alcoholysis is 88%.

[0031] Example 1 The present embodiment provides a hydrophilic wear-resistant photovoltaic coating with a photocatalytic effect, wherein the raw materials include, by mass, 0.3 parts of hydrophilic nano-silicon dioxide, 0.5 parts of hydrophilic nano-zirconia, 2 parts of hydrophilic nano-titanium dioxide, 0.3 parts of polyvinyl alcohol, 0.08 parts of glutaraldehyde, and 90 parts of ethanol. The average particle size of the hydrophilic nano-silicon dioxide is 10 nm, the average particle size of the hydrophilic nano-zirconia is 30 nm, and the average particle size of the hydrophilic nano-titanium dioxide is 20 nm.

[0032] A method for preparing a hydrophilic, wear-resistant photovoltaic coating with a photocatalytic effect in this embodiment comprises the following steps: S1, putting hydrophilic nano-silicon dioxide, hydrophilic nano-zirconium oxide and hydrophilic nano-titanium dioxide into ethanol to obtain an inorganic powder suspension; S2, mixing polyvinyl alcohol with distilled water, dissolving the polyvinyl alcohol in a water bath at 98° C., to obtain a polyvinyl alcohol aqueous solution with a mass concentration of 12%; S3, adding the polyvinyl alcohol aqueous solution to the inorganic powder suspension to obtain a mixed solution, adjusting the pH value of the mixed solution to 4, adding glutaraldehyde, and stirring to obtain a spray solution; S4. Spray the spray solution onto the photovoltaic panel. During the spraying process, the pressure of the spray gun is 0.2 MPa, the distance between the spray gun and the sprayed surface is 25 cm, and after cross-linking and curing at room temperature for 24 hours, a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect and a thickness of 80 nm is obtained.

[0033] The SEM image of the hydrophilic wear-resistant photovoltaic coating with photocatalytic effect in this embodiment is as follows: Figure 1 The hydrophilic and wear-resistant photovoltaic coating with photocatalytic effect in this embodiment is applied to the photovoltaic panel, and bird droppings fall on the photovoltaic panel, as shown in FIG. Figure 2 As shown in Figure 1, the decomposition of bird droppings after 7 days is as follows: Figure 3 As shown, it can be seen that the photovoltaic coating in this embodiment has a good self-cleaning effect.

[0034] Example 2 This embodiment provides a hydrophilic wear-resistant photovoltaic coating with a photocatalytic effect, wherein the raw materials include, by mass, 0.8 parts of hydrophilic nano-silicon dioxide, 1 part of hydrophilic nano-zirconia, 2.5 parts of hydrophilic nano-titanium dioxide, 0.5 parts of polyvinyl alcohol, 0.1 parts of glutaraldehyde, and 90 parts of ethanol. The average particle size of the hydrophilic nano-silicon dioxide is 20 nm, the average particle size of the hydrophilic nano-zirconia is 60 nm, and the average particle size of the hydrophilic nano-titanium dioxide is 30 nm.

[0035] A method for preparing a hydrophilic, wear-resistant photovoltaic coating with a photocatalytic effect in this embodiment comprises the following steps: S1, putting hydrophilic nano-silicon dioxide, hydrophilic nano-zirconium oxide and hydrophilic nano-titanium dioxide into ethanol to obtain an inorganic powder suspension; S2, mixing polyvinyl alcohol with distilled water, dissolving the polyvinyl alcohol in a water bath at 100° C., and obtaining a polyvinyl alcohol aqueous solution with a mass concentration of 18%; S3, adding a polyvinyl alcohol aqueous solution to the inorganic powder suspension to obtain a mixed solution, adjusting the pH value of the mixed solution to 6, adding glutaraldehyde, and stirring to obtain a spray solution; S4. Spray the spray solution onto the photovoltaic panel. During the spraying process, the pressure of the spray gun is 0.4 MPa, the distance between the spray gun and the sprayed surface is 15 cm, and after cross-linking and curing at room temperature for 24 hours, a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect and a thickness of 120 nm is obtained.

[0036] Example 3 This embodiment provides a hydrophilic wear-resistant photovoltaic coating with a photocatalytic effect, wherein the raw materials include, by mass, 0.5 parts of hydrophilic nano-silicon dioxide, 0.7 parts of hydrophilic nano-zirconia, 2.2 parts of hydrophilic nano-titanium dioxide, 0.4 parts of polyvinyl alcohol, 0.09 parts of glutaraldehyde, and 90 parts of ethanol. The average particle size of the hydrophilic nano-silicon dioxide is 15 nm, the average particle size of the hydrophilic nano-zirconia is 40 nm, and the average particle size of the hydrophilic nano-titanium dioxide is 25 nm.

[0037] A method for preparing a hydrophilic, wear-resistant photovoltaic coating with a photocatalytic effect in this embodiment comprises the following steps: S1, putting hydrophilic nano-silicon dioxide, hydrophilic nano-zirconium oxide and hydrophilic nano-titanium dioxide into ethanol to obtain an inorganic powder suspension; S2, mixing polyvinyl alcohol with distilled water, dissolving the polyvinyl alcohol in a water bath at 99° C., to obtain a polyvinyl alcohol aqueous solution with a mass concentration of 16%; S3, adding the polyvinyl alcohol aqueous solution to the inorganic powder suspension to obtain a mixed solution, adjusting the pH value of the mixed solution to 5, adding glutaraldehyde, and stirring to obtain a spray solution; S4. Spray the spray solution onto the photovoltaic panel. During the spraying process, the pressure of the spray gun is 0.3 MPa, the distance between the spray gun and the sprayed surface is 20 cm, and after cross-linking and curing at room temperature for 24 hours, a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect and a thickness of 100 nm is obtained.

[0038] Comparative Example 1 This comparative example is the same as Example 1, except that an equal amount of hydrophilic nano-titanium dioxide is replaced by zinc oxide (ZnO) nanoparticles.

[0039] Comparative Example 2 This comparative example is the same as Example 1, except that an equal amount of hydrophilic nano-zirconia is replaced by hydrophilic nano-alumina of equal size (Hangzhou Jikang New Materials Co., Ltd.; CAS No. 1344-28-1).

[0040] The coatings in Examples 1-3 and Comparative Examples 1-2 were tested for wear resistance using a Taber abraser. A CS-10F grinding wheel was used, a load of 150 g was applied, and the abraser speed was set to 60 rad / min. After the wear was completed, the contact angle and light transmittance effect of the worn area were measured. The wear resistance of the coating was evaluated by the total number of revolutions at which the worn area still maintained superhydrophilicity and light transmittance. The measurement results are shown in Table 1.

[0041] Table 1 Wear resistance test results The coatings in Examples 1-3 and Comparative Examples 1-2 were subjected to self-cleaning and antifouling tests, and the decomposition results of bird feces were measured after 1 day, 3 days, 5 days, and 7 days, respectively. The test results are shown in Table 2.

[0042] Table 2 Bird feces decomposition test results It can be seen from the data in the table that the coating of the present invention has a good effect of decomposing bird droppings.

[0043] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A hydrophilic wear-resistant photovoltaic coating with photocatalytic effect, characterized in that: The raw materials include hydrophilic nano silicon dioxide, hydrophilic nano zirconium oxide, hydrophilic nano titanium dioxide, polyvinyl alcohol, glutaraldehyde and ethanol.

2. The hydrophilic and wear-resistant photovoltaic coating with photocatalytic effect according to claim 1, characterized in that: The raw materials include 0.3-0.8 parts of hydrophilic nano silicon dioxide, 0.5-1 parts of hydrophilic nano zirconium oxide, 2-2.5 parts of hydrophilic nano titanium dioxide, 0.3-0.5 parts of polyvinyl alcohol, 0.08-0.1 parts of glutaraldehyde and 90 parts of ethanol by weight.

3. The hydrophilic and wear-resistant photovoltaic coating with photocatalytic effect according to claim 1, characterized in that: The average particle size of the hydrophilic nano-silicon dioxide is 10-20 nm.

4. The hydrophilic and wear-resistant photovoltaic coating with photocatalytic effect according to claim 1, characterized in that: The average particle size of the hydrophilic nano titanium dioxide is 20-30 nm.

5. A method for preparing a hydrophilic and wear-resistant photovoltaic coating with photocatalytic effect according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Put hydrophilic nano-silicon dioxide, hydrophilic nano-zirconium dioxide and hydrophilic nano-titanium dioxide into ethanol, and obtain an inorganic powder suspension by ultrasonic crushing and mechanical grinding; S2, mixing polyvinyl alcohol with distilled water, dissolving the polyvinyl alcohol under a water bath condition, and obtaining a polyvinyl alcohol aqueous solution; S3, adding the polyvinyl alcohol aqueous solution to the inorganic powder suspension to obtain a mixed solution, adjusting the pH value of the mixed solution, adding glutaraldehyde, and stirring to obtain a spray solution; S4, spraying the spray solution onto the photovoltaic panel, and obtaining a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect after cross-linking and curing.

6. The method for preparing a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect according to claim 5, characterized in that: The mass concentration of the polyvinyl alcohol aqueous solution in S2 is 12-18%.

7. The method for preparing a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect according to claim 5, characterized in that: The water bath temperature in S2 is 98-100°C.

8. The method for preparing a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect according to claim 5, characterized in that: The pH value described in S3 is 4-6.

9. The method for preparing a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect according to claim 5, characterized in that: During the spraying process described in S4, the pressure of the spray gun is 0.2-0.4 MPa, and the spray distance is 15-25 cm.

10. The method for preparing a hydrophilic and wear-resistant photovoltaic coating with a photocatalytic effect according to claim 5, characterized in that: The thickness of the hydrophilic wear-resistant photovoltaic coating with photocatalytic effect is 80-120 nm.